Analisis Strategi Peningkatan Penerimaan Pajak Hiburan Pada Badan Pendapatan Daerah Dki Jakarta Tahun 2019 - Aldi Saputra; Novianita Rulandari (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The phenomenon of this research is that entertainment tax revenue in DKI Jakarta has not been maximized. this is because there is still a lack of awareness of taxpayers and entertainment tax collection that has not been running optimally. This study aims to determine the analysis of strategies for increasing entertainment tax revenue in DKI Jakarta. This research method uses descriptive qualitative methods, with data collection techniques through observation, documentation and interviews. Data sources consist of primary data and secondary data. The results of this study indicate: (1) the strategy for entertainment tax revenue can be increased due to cooperation with other agencies and extensification of entertainment tax objects, as well as monitoring and collection. (2) the obstacle is the lack of awareness of taxpayers and resources, and (3) the efforts that have been made, namely by increasing the quality and quantity of resources both within the organization and the taxpayer itself.